Tetravalent Doping of CeO2: The Impact of Valence Electron Character on Group IV Dopant Influence. Issue 1 (28th November 2013) - Vanpoucke, D. E. P.; Cottenier, S.; Van Speybroeck, V.; Van Driessche, I.; Bultinck, P.
Abstract : Fluorite CeO2 doped with group IV elements is studied within the density functional theory (DFT) and DFT +  U framework. Concentration‐dependent formation energies are calculated for Ce1− x Z x O2 (Z = C, Si, Ge, Sn, Pb, Ti, Zr, Hf) with 0 ≤  x  ≤ 0.25 and a roughly decreasing trend with ionic radius is observed. The influence of the valence and near valence electronic configuration is discussed, indicating the importance of filled d and f shells near the Fermi level for all properties investigated. A clearly different behavior of group IVa and IVb dopants is observed: the former are more suitable for surface modifications and the latter are more suitable for bulk modifications. For the entire set of group IV dopants, there exists an inverse relation between the change, due to doping, of the bulk modulus, and the thermal expansion coefficients. Hirshfeld‐I atomic charges show that charge‐transfer effects due to doping are limited to the nearest‐neighbor oxygen atoms.